The Magic of M.C. Escher - Escher, M.C. (Maurits Cornelis) (London : Thames&Hudson, 2006)
Presents a selection of drawings and prints by twentieth-century Dutch artists M.C. Escher, each accompained by comments and explanations by the artists.
Keywords: Escher, M.C., -- 1898-1972 -- Catalogs